Depressive symptoms in caregivers immediately after stroke. Issue 3 (3rd April 2019) - Byun, Eeeseung; Evans, Lois; Sommers, Marilyn; Tkacs, Nancy; Riegel, Barbara
ABSTRACT: Background : Caregivers of stroke survivors often suffer depressive symptoms that interfere with their own health. Early recognition may lead to attenuation of symptoms and better health and well-being for caregivers. Objective : We examined characteristics of caregivers and stroke survivors associated with caregivers' depressive symptoms in the early poststroke period. Methods : We conducted a prospective, longitudinal exploratory observational study with a convenience sample of 63 caregivers of older adult (≥ 65 years) stroke survivors recruited from urban acute-care settings. We enrolled caregivers by 2 weeks poststroke (T1) and revisited them 4 weeks later (T2). Depressive symptoms were measured using the Patient Health Questionnaire-9. A separate unadjusted linear mixed model was computed to explore significant associations between each caregiver or stroke-survivor characteristic and depressive symptoms. Results : Caregivers, on average, reported mild depressive symptoms at T1 and T2. Each of the following characteristics was independently associated with caregiver depressive symptoms over the first 6 weeks poststroke: caregiver uncertainty ( p < 0.001), perceived stress ( p < 0.001) but not cortisol levels ( p = 0.858 on waking, p = 0.231 evening), coping ( p < 0.001), social support ( p = 0.006), race ( p = 0.022), income ( p = 0.001), time spent on care ( p = 0.039), and stroke-survivor race ( p = 0.033) and functional status ( p = 0.003). At T2, caregiver depressive symptoms were correlated with evening cortisol level ( p = 0.001). Conclusions : Caregiver and stroke-survivor characteristics may help identify caregivers at highest risk for early depressive symptoms and guide interventions aimed at their resolution.